2016
DOI: 10.1016/j.chemgeo.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the reduction of chromium(VI) on magnetite surfaces using in situ electrochemical AFM

Abstract: Hexavalent chromium is a highly toxic and readily mobile metal contaminant introduced to the environment through a variety of industrial operations. In the presence of reductants, such as Fe(II), and catalytic mineral surfaces, such as iron oxides surfaces, Cr(VI) may be reduced to a less toxic and relatively insoluble form Cr(III). In this study, we investigate the interaction between Cr(VI) and the surface of the Fe(II)-bearing mineral magnetite, Fe(II)Fe(III) 2 O 4 , as an example catalyst, using electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…To minimize the 60 Hz noise from the power line, all cables were co-axially shielded and all electrical grounds were common to the bipotentiostat (CHI760D, CH Instrument, Texas, USA) that was used for controlling the electrochemical conditions. A Bruker EC-AFM cell [37] was used for PeakForce SECM imaging. In this cell, a Pt wire loop along the internal perimeter of the cell was used as a counter electrode and a AgCl-coated Ag wire was used as a pseudo-reference electrode (AgQRE).…”
Section: Peakforce Secmmentioning
confidence: 99%
“…To minimize the 60 Hz noise from the power line, all cables were co-axially shielded and all electrical grounds were common to the bipotentiostat (CHI760D, CH Instrument, Texas, USA) that was used for controlling the electrochemical conditions. A Bruker EC-AFM cell [37] was used for PeakForce SECM imaging. In this cell, a Pt wire loop along the internal perimeter of the cell was used as a counter electrode and a AgCl-coated Ag wire was used as a pseudo-reference electrode (AgQRE).…”
Section: Peakforce Secmmentioning
confidence: 99%
“…This result revealed the presence of precipitated Cr 2 O 3 species on the α-FeOOH surface at pH 3. 55 It was noticeable that a high CrO(OH) content in Cr@Fe 3 O 4 might proceed through Cr 3+ migration on the Fe 3 O 4 surface.…”
Section: Resultsmentioning
confidence: 99%
“…21 Surface Coverage and Volumetric Analyses of AFM Images. Image analyses were performed for the two samples shown in Figures 1 and 2 using an in-house developed MATLAB script (described in Walker et al 37 ) to quantify adsorbates observed on the AFM images. This script's binary images (Figure 5a−c) show the adsorbate distribution patterns and surface coverages on the calcite surface by using white dots on a black background.…”
Section: ■ Resultsmentioning
confidence: 99%